Intranasal Trans-Sialidase Vaccine Mitigates Acute and Chronic Pathology in a Preclinical Oral Chagas Disease Model - Pacini, María Florencia (2024)
Chagas disease, caused by Trypanosoma cruzi, leads to severe complications in 30% of infected individuals, including acute myocarditis and chronic fibrosing cardiomyopathy. Despite the significant burden of this disease, there is currently no licensed vaccine available to prevent it. This study aimed to evaluate the mucosal and systemic immunogenicity as well as the prophylactic efficacy of a mucosal vaccine candidate and its impact on both acute and chronic cardiomyopathy. The results showed that the nasal administration of trans-sialidase (TS) plus c-di-AMP (TS+A) vaccine elicited a NALT expression of IFN-γ, IL-17a and IL-4 mRNA as well as a nasal-specific production of IgA. An in vivo challenge with TS also triggered increased proliferation of lymphocytes from the NALT, sentinel cervical lymph node, and spleen. TS+A immunization increased the plasma levels of Th1/Th2/Th17 cytokines and elicited an evident cellular response by which to judge enhanced delayed-type hypersensitivity responses following a TS footpad challenge. After oral infection, TS+A-vaccinated mice showed significantly reduced parasitemia and parasite load in the heart, muscles and intestines, while markers of hepatic and muscle damage as well as clinical manifestations of acute infection were strongly diminished. TS+A also attenuated acute myocarditis and the expression of inflammatory markers in the heart. The protection conferred by TS+A extended into the chronic phase, where it resulted in a clear reduction in chronic myocarditis, fibrosis and functional electrocardiographic abnormalities, associated with a decreased expression of the profibrotic TGF-β. These results revealed that it is possible to develop a mucosal vaccine against T. cruzi based on TS and c-di-AMP that is capable of reducing the development of Chagas cardiomyopathy, the hallmark of Chagas disease.